Improved biogas production by anaerobic co-digestion of whey and bovine manure: A case study in Montevideo-Peru - Camacho Alvarez, Daniela Geraldine; Chávez García, Johann Alexis; Lama Bustinza, José Carlos; Rodríguez Rodríguez, Berlan; Castillo Alvarez, Yoisdel; Jiménez Borges, Reinier (LACCEI, 2025)
Improved biogas production through anaerobic co-digestion of cattle manure and whey is presented as a viable strategy for energy sustainability, especially in rural environments. Despite its potential, there are limitations related to the proper selection of mixing ratios and the design of biodigesters, which impacts the efficiency of the process. This descriptive and experimental research addresses these limitations by evaluating the 80:20 (manure: whey) mixture and incorporating innovations such as a manual agitator and a greenhouse that maintains stable mesophilic conditions at 37 °C. In the study, the average daily production is about 42.78 liters of CH2 per kilogram of organic matter, with a methane content of 54.2%, exceeding theoretical predictions by 12.3%. Likewise, the resulting digestate presented an average NPK ratio of 1.75-0.5-0.25 g/l, increasing agricultural yields by 20 %. From the environmental point of view, a mitigation of 2.6 tons of CO 2 equivalent per year was achieved, highlighting the contribution of the system in the reduction of greenhouse gas emissions. This methodological approach demonstrates the technical, environmental and economic viability of co-digestion, offering a replicable and sustainable solution for rural communities. The results obtained reaffirm the importance of improving the design and operation of biodigesters, highlighting their potential to promote a circular economy model with positive impacts at the local and regional scale.